Highly Substituted Δ3‐1, 2, 3‐Triazolines: Solid‐State Emitters with Electrofluorochromic Behavior. Issue 27 (26th April 2019) - Suleymanov, Abdusalom A.; Ruggi, Albert; Planes, Ophélie Marie; Chauvin, Anne‐Sophie; Scopelliti, Rosario; Fadaei Tirani, Farzaneh; Sienkiewicz, Andrzej; Fabrizio, Alberto; Corminboeuf, Clémence; Severin, Kay
Abstract: Highly substituted Δ 3 ‐1, 2, 3‐triazolines can be prepared by reaction of triarylvinyl Grignard reagents with functionalized organic azides. The heterocycles are fluorescent in the solid state, and—depending on the substituents—they can display aggregation‐induced emission. Upon oxidation, the triazolines form stable radical cations with altered photophysical properties. Therefore, they represent rare examples of solid‐state emitters with intrinsic electrofluorochromic behavior. Abstract : Light up your chemistry ! Redox‐switchable fluorophores (see scheme) based on highly substituted Δ 3 ‐1, 2, 3‐triazolines were obtained by reaction between vinyl Grignard reagents and organic azides.